Qur’anic Hermeneutics and the Ecological Crisis: A Thematic Ecotheological Reconstruction of Cosmic Balance - Abdul Syukkur (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2026)
The escalating global environmental crisis demands a profound ontological and normative shift beyond conventional materialistic and technocratic paradigms. This study examines the conceptual construction of ecological stewardship within Islamic scripture to address contemporary environmental degradation. The unit of analysis comprises specifically selected Qur’anic verses addressing cosmic equilibrium, terrestrial preservation, and human-nature interactions. This research aims to systematically reconstruct Qur’anic environmental ethics by identifying core ethical formulations, examining the structural causes of their contemporary neglect, and evaluating their implications for long-term ecological sustainability. Employing a qualitative research design, this study synthesizes thematic interpretation (tafsīr mawḍū‘ī) with a systematic ecotheological analytical framework. The findings reveal that Qur’anic environmental ethics are anchored in an interdependent matrix of cosmic balance (mīzān), divine trust (amānah), existential stewardship (khilāfah), and an absolute prohibition of systemic corruption (fasād). Furthermore, the investigation demonstrates that contemporary ecological neglect is fundamentally driven by moral-spiritual decay, reductionist anthropocentric exegetical frameworks, and the utilitarian co-optation of scriptural texts to legitimize resource exploitation. The novelty of this research lies in its formulation of an integrated ecotheological framework that bridges metaphysical realities with empirical sustainability paradigms. This study contributes to global Islamic ecological discourse by offering a non-anthropocentric conceptual model that harmonizes traditional exegesis with contemporary sustainability challenges.